Imaging of small-scale faults in seismic reflection data: Insights from seismic modelling of faults in outcrop. (January 2023) - Dimmen, Vilde; Rotevatn, Atle; Lecomte, Isabelle
Abstract: Faults with throws that fall below vertical seismic resolution are challenging to identify in reflection seismic datasets. Nevertheless, such small-scale faults may still affect the seismic images, and in this study, we build seismic models of outcrop analogues to investigate how . Using photogrammetry from faults affecting Oligocene to Miocene carbonate rocks in Malta, we build a series of geological models from which synthetic seismic images are produced. The resulting seismic images are analysed to elucidate the effects of varying geologic input, signal properties and introduction of noise, and compared to real seismic data from the SW Barents Sea, offshore Norway. Our results suggest that at signal peak frequencies of 30 Hz and higher, using the classic Ricker wavelet type and without introducing noise, graben forming faults with a combined displacement down to ∼5 m affect the seismic image by slight downwarping of reflections, whereas single faults with displacement down to ∼10 m show detectable non-discrete reflection offsets in form of a monoclinal geometry at signal peak frequencies at 60 Hz. Using an Ormsby wavelet, we get seismic images with a quality that lie in between that of the 30 Hz and 60 Hz Ricker, even though the peak frequency is lower. The identified structures can also be seen when noise is included, although the reflections are more irregular and harder to detect. This suggests that under relatively noise-free conditions in high-quality reflection seismic datasets, lower-throw faults (as low as 5 m in this study) that do not induce discrete reflection offsets in seismic images may still produce reflection distortions. Additionally, seismic modelling using the Ormsby wavelet, and its effect on the seismic image, is lacking in literature as of today. We suggest that the results and examples shown in this study may be used to geologically inform fault interpretations in real seismic datasets and may form an empirical basis for geologically concept-driven fault interpretation strategies. Highlights: Seismic modelling used to investigate the effect of small-scale faults (D = 1–20 m). Faults with displacement down to 5 m may cause distortions to reflections. Faults (D = 11–20 m) may cause discrete offsets or monoclinal shape of reflections. Results can be used to inform fault interpretations in real seismic datasets.